PENGARUH PEMAHAMAN SAK EMKM, LATAR BELAKANG PENDIDIKAN, DAN UKURAN USAHA TERHADAP KUALITAS LAPORAN KEUANGAN UMKM - Zennita, Laurencia; Marlina, Evi; Fitriana, Nur (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2025)
The study aims to find out and analyze whether understanding of SAK EMKM, educational background, and business size influence the quality of MSME financial reports in Pekanbaru City. The method used in research is quantitative. Primary data was collected using a questionnaire. The entire Pekanbaru MSME population was included in the research. The sampling approach used in this research is random sampling based on the Slovin formula. The research results explain that understanding EMKM SAK, educational background, and business size all influence the quality of MSME financial reports.